Revisiting how the Javanese traditional food safety practice significantly reduces cyanide concentration of marketed cassava roots - Wresti L. Anggayasti; Sri Herminingrum; Andi Kurniawan (Hasanuddin University Food Science and Technology Study Program, 2022)
Despite being one of the most popular staple foods in Indonesia, cassava roots contain cyanide that can cause death without proper processing. In traditional market, however, the variant of the roots, hence their exact cyanide concentration, is mostly unknown. Despite that, Javanese have successfully been curbing the cassava poisoning risk through generations. To revisit the role of the local food safety practice in reducing the cyanide concentration, this study investigated and simulated how Javanese in Malang Regency, East Java, Indonesia, traditionally prepare cassava roots for consumption. Two commonly marketed roots; white and yellow; were selected and cooked by steaming or roasting. The cyanide concentration of each stage was measured by picric acid method optimized for cassava roots. The analyses demonstrated that 30 min steaming peeled roots, as well as 50 min steaming and 30 min roasting the unpeeled roots reduced the cyanide content to 12-18 ppm, below the Indonesian acceptable limit of 40 ppm. The cooking duration and temperature of 100-230oC together contributed to decrease the cyanide concentration. Our findings concluded that Javanese applied traditional food safety management through the farmers’ preference to cultivate cassava with low cyanide level, the selection of fresh roots, and the cooking methods.